Palmaris longus absence in six largest Indonesian ethnicities and its relationship with gender, ethnicity, and hand dominance (Medical Journal of Indonesia, 2015)
Background: Palmaris longus (PL) tendon is often used as graft in tendon or ligament reconstruction. PL absence is a normal variation in human body. Its prevalence was different in various population. Serbian population had an absence rate of 42.4%, but in the Korean population it was only 4.0%. This study aimed to determine the prevalence of PL absence in various ethnic of Indonesian population and its relationship with gender and side of hand dominance. Methods: We conducted a cross-sectional study in 1230 people from six ethnicities in Indonesia. The absence of PL was determined by Schaeffer test and confirmed with Mishra and Thompson test. Data collection was performed by a single examiner in various cities in Indonesia. The relationship between PL absence with ethnicity, gender, and hand dominance were determined by Chi-square test. Results: Prevalence of PL absence in overall Indonesian population was 10.4% (bilateral 37.5% and unilateral 62.5%). The highest were in Batak and Madura ethnicities (15.5%), followed by Sunda (11.8%), Java (10.0%), Betawi (6.0%), and the lowest was Minang ethnicity (4.1%) (p = 0.008). Prevalence of PL absence in female and male were 10.7% 10.2%, respectively, p > 0.05). Conclusion: Compared to range of prevalence in other countries in the world, prevalence of PL absence in Indonesian population was moderate (10.4%). There was significant difference found between ethnicity, but not in gender. Surgeon should consider this data when planning for reconstruction procedures using PL graft in Indonesian population.